Mental Health of Healthcare Workers During the Third Wave of the COVID-19 Pandemic: Did We Forget them after the First Wave? - Mahdieh Saeri; Atefeh Vaezi; Negah Tavakolifard; Shaghayegh Haghjooy Javanmard (Advanced Biomedical Research, 2023)
Background: Since December 2019, countries experienced different numbers of COVID-19 pandemic waves. The COVID-19 pandemic led to adverse psychologic problems in the communities and among healthcare workers (HCWs), but the dynamic of these problems through different waves needs to be established more. Materials and Methods: This cross-sectional study was conducted in October 2020, through the third wave of the COVID-19 pandemic, in Isfahan, Iran. We studied HCWs' depression, anxiety, and stress using Depression, Anxiety, Stress Scale-21 (DASS-21) and insomnia using Insomnia Severity Index (ISI) questionnaires. Multiple linear regression was used to evaluate the association of some characteristic factors with different psychologic symptoms. Results: Our results showed that about 80% of HCWs had one or more psychological problems. The prevalence of depression, anxiety, stress, and insomnia was 46.0%, 50.2%, 44.6%, and 66.5%, respectively. Female sex, working in ICU, and having a history of chronic disease were predictors of psychological symptoms in our participants. Conclusion: HCWs' mental health state could be underestimated or neglected. The third pandemic wave negatively affected the mental health of the HCWs. Since mental health problems of HCWs may reduce the quality of care, the potential impact of not addressing this issue should be highlighted.